EVALUATION OF MEDICINAL PLANTS (ASTRAGALUS ERIOCEPHALUS AND QUERCUS INFECTORIA) AS FEED ADDITIVES IN AWASSI EWES’ RATION 2. SOME BLOOD BIOCHEMICAL, HORMOAL LEVELS AND MILK HYIGEN. - & et al., Barwary (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study was to investigate the effect of addition two medical plants or their mixture on hematological, biochemical parameters, hormonal levels and milk microbiology of lactating Awassi ewes. Twenty-eight ewes at mid lactation were divided into four groups and fed rations containing 1% Gall oak, 2% Astragalus, 0.5 Gall oak + 1% Astragalus, and Control. At biweekly intervals, blood samples were withdrawn. A bulk milk samples was collected for microbiological test under sterilized conditions. Results revealed that medicinal plants significantly influenced Erythrocyte Sedimentation Rate being lowest in the Astragalus group. Ewes feed Mixture group had significantly higher blood glucose concentration. Cholesterol level was significantly lower in the blood of ewes fed Gall oak diet and was highest in ewes fed Astragalus diet. Animals fed diet supplemented with Gall oak had a significantly higher concentration of T3 hormone. Total viable bacterial and mold count was decreased in the milk of Astragalus and Gall oak group, respectively. It can be concluded that Astragalus eriocephalus and Quercus infectoria improved immunity, metabolism and milk hygiene of lactating Awassi ewes.